Use of translation in the writings of International students learning English in Malaysia / Soheila Mahernia - Mahernia, Soheila (2014)
There are increasing numbers of international students coming to Malaysia every year. One of the problems they face while they are learning English in ESL classrooms is to know whether it is beneficial or not for them to use their native language and translation as a tool for learning the second language. Second language researchers have also currently started to re-evaluate the role of translation and first language (L1) in ESL classrooms. This research was based primarily on an examination of direct and indirect (translated) essay writing in English by 25 college students from different Russian speaking countries having pre advanced and advanced level of English proficiency. The intension of this research is to investigate the quality of students’ writing with and without the use of translation by comparing and analysing their written output linguistically. The main research question in this study is: “How does translation help international students to improve their ESL essay writing?” For the purpose of triangulation, two questionnaires were used, one for the participants and another one for their instructors regarding their beliefs about the use of translation in ESL writing in order to answer the second research question: “What do the students’ think about the use of translation and mother tongue or L1 considering it to be a tool for ESL learning?” and the third research question : “What do the students’ instructors think about the use of translation and L1 in ESL classrooms?” An oral interview was also conducted to find out about the students’ beliefs regarding the use of translation in second language learning. The interview was recorded and transcribed accordingly. The results show that pre advanced (60%) students benefited more from translation than the advanced students. In the case of the advanced students’ writing there was no significant amount of change in their two writing products. The findings also show that iv majority of the participants (14), believed that with the use of translation they could write English compositions much better. Considering their instructors’ beliefs, it was observed by the reactions of their two teachers belonging to two different generations that nowadays some teachers of the new generation have started to realize the importance of using the L1 in second language learning. On the other hand, the older generation of ESL teachers regard the use of the L1 and translation in the classrooms as a taboo. The conclusions reached were that both pre advanced and advanced students in their translated writings had traces of Russian dominance according to the Russian translators assisting the researcher in the analysis of the writings. Hence, it is beneficial for the students that their instructors in ESL classrooms provide them suggestions on how the systematic use of translation can serve them. They should be guided to organize their ideas and provide information in a lexically and grammatically acceptable and appropriate way. In fact the findings suggest that there should be a focus on how these students select appropriate vocabulary both for their direct and indirect writing as well as learning to prevent their L1 from dominating their L2 lexis and syntax. Keywords: translation, mother tongue, first language (L1), student beliefs, language analysis, English as a Second Language (ESL), writing.